Elicitive Conflict Mapping - Dietrich, Wolfgang (Many Peaces, 2018)
There are not many books that I have read cover to cover - Many Peaces is one of these. I now think of peace and conflict transformation in different ways, and I will be eternally grateful to Dietrich for lifting me out of the confusion and disillusionment that I was experiencing as a peace educator before his book presented itself to me in the University of Cambridge Library. Hilary Cremin - University of Cambridge, UK The read itself is a transrational, systems journey that requires analysis, synthesis, meditation, and reflection. Practical aspects of this book, specifically film analysis, are helpful to see how elicitive conflict mapping can be applied to understanding real world conflict and suffering. Edward J. Brandmeier - James Madison University, USA This volume provided me with a refreshing view and an opening of thought, resulting in a confident shift in approach towards leader and teacher preparation. The rich, personal and humble storytelling that drew me in at the beginning, liberated me at the final word. Heidi Smith - University of Tasmania, Australia Wolfgang Dietrich is the foremost thinker in the field of peace studies. Gustavo Esteva - Rector Emeritus, Universidad de la Tierra, Mexico This book completes Wolfgang Dietrich's path-breaking trilogy of the Many Peaces; the foundation of the highly innovative approach to peace and conflict as taught and applied at the University of Innsbruck, Austria. Where Volume 1 elaborated the transrational philosophy of the many peaces and Volume 2 discussed the curricular and didactic aspects of elicitive conflict transformation (ECM), Volume 3 provides principles and examples of ECM's practical application. The author drafts the easy use of ECM as a brand new method of conflict work that can be applied from both intra and interpersonal conflicts to the highest political and diplomatic level. This book would form an excellent basis for leadership and relationship training of future peace workers within the frame of elicitive conflict transformation. .